Time Argonaut: A Game to Practice Telling Time in English for Rural School Students - Annavelle, Munga Dicky; Bong S., Fen; Harrison K. K., S.; Hephzibah, R. Sangen; Nadia, Raca; Ng Kia, Jee (UNIMAS Publisher, 2023)
This article describes the design and development of an educational game for primary school students in a rural area of Sarawak. Students from rural Sarawak areas face several challenges contributing to demotivation when learning Mathematics and Sciences, including poor English proficiency, limited accessibility to the internet and gadgets, lack of genuine opportunities to practice English in real life, and teachers' English proficiency. In this study, a gamified learning module was designed to teach about time and tailored to students' needs. 25 Primary One students from a rural Baram, Sarawak school were recruited through crowdsourced convenience sampling for the study. Playday was conducted with the students to collect their feedback, and results were obtained from observation and feedback. Results from the playday showed that the students perceived that the game was fun and motivated them to learn about clock reading and time, engaging them to collaborate in learning and promoting teamwork in learning. The integration of gamification in teaching creates a meaningful learning process for students. It is recommended to examine the effectiveness of gamification at the secondary school level in future studies and explore the effectiveness of different game designs and game mechanisms